2022
DOI: 10.1108/k-03-2022-0430
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of the tourism supply chain in the 21st century: a bibliometric analysis

Abstract: PurposeThis study aims to examine the evolution of the tourism supply chain (TSC) and its future development factors. To this end, a quantitative bibliometric analysis was conducted to provide insights from a statistical perspective, including the evolution of the TSC and an outlook on current characteristics and future research trends.Design/methodology/approachThis paper presents a quantitative bibliometric study of selected papers on the Web of Science. The study of the evolution of the TSC is based on anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…This study makes several practical and conceptual contributions to the tourism management literature. Furthermore, in addressing extant research gaps identified in contemporary research (e.g., Alkier et al, 2022; Jain et al, 2022; Szpilko, 2017), the study empirically examined various key themes pertaining to SC stakeholders in the context of two firms currently seeking to develop their tourism activities and offerings. Importantly, both firms operate in Da Lat, Vietnam, a popular tourist destination and in two industries with potential for tourism development (e.g., Candelo et al, 2019; Holroyd & Coates, 2021; Luo et al, 2021; Nghiêm‐Phú et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study makes several practical and conceptual contributions to the tourism management literature. Furthermore, in addressing extant research gaps identified in contemporary research (e.g., Alkier et al, 2022; Jain et al, 2022; Szpilko, 2017), the study empirically examined various key themes pertaining to SC stakeholders in the context of two firms currently seeking to develop their tourism activities and offerings. Importantly, both firms operate in Da Lat, Vietnam, a popular tourist destination and in two industries with potential for tourism development (e.g., Candelo et al, 2019; Holroyd & Coates, 2021; Luo et al, 2021; Nghiêm‐Phú et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, and more recently, Jain et al (2022) acknowledge the unexplored/understudied nature of research on resilient tourism and hospitality SCs in the COVID‐19 era. Third, while the SC literature predominantly focuses on the flow of physical goods and products, or the management of orders, there is an absence of research and publications on this field in tourism (Alkier et al, 2022). Fourth, an additional literature review conducted for the present research confirms that research on emerging economies' TSCs is scant; this gap is also obvious in the context of (a) firms seeking to develop their tourism offerings, and (b) firms' relationships with their SC stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, management rationalises operations, introduces a business model of lean management, reduces overhead costs and optimises costs related to external suppliers (Crepi et al, 2021); (ii) diversification of income streams during crises can mitigate risk and reduce dependence on a single source (alternative options for monetising assets, introduce new services/products, and change supply chain management (new suppliers, shorter delivery routes, new markets for finding guests, etc.) (Alkier, Milojica & Roblek, 2023;Strange, 2020); (iii) crisis communication with stakeholders, because maintaining good relations with stakeholders is considered to be of key importance in times of crisis (Ritchie, 2004); (iv) Digital transformation, because crises and the Covid-19 crisis were no exception, sped up the introduction of digital solutions in hotel operations (Sharma, Thomas & Paul, 2021); (v) cooperation (formation of consortia and acquisitions as a form of ownership takeover) enables hotels (specially hotel chains) and other tourism firms to acquire the human resources they lack, gain new professional skills, access new segments of guests and suppliers, and new innovative solutions (Konovalova et al, 2020); (vi) focusing on the main services that guests demand the most or to satisfy critical needs. For this purpose, the management has the opportunity to transform the offer, change existing resources or introduce solutions that are intended to specifically address the emerging demands of guests during the crisis (the need for sustainable and green solutions) (Mzembe et al, 2021); (vii) use of government support measures -for business liquidity and keeping the current level of headcount which almost all hotel companies used (González-Torres et al, 2021); (viii) scenario planning and risk management because crisis business models include robust scenario planning and risk management (Sax & Andersen, 2019); (ix) sustainable practices and social responsibility because the time of crisis raises the awareness and importance of sustainable business models and social responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…32 (2025) in terms of safety, services, and resources in order to achieve higher profits. The fulfillment of this objective is not trivial and requires the optimization of strategical, tactical, and operational decisions made at any point of the tourism chain (Alkier et al, 2023). It is necessary to organize and coordinate several "logistics nodes," including booking sites, airports, stations, hotels, and places of interest.…”
Section: Introductionmentioning
confidence: 99%